Preferences for redistribution in Latin America - Matias Busso; Ana María Ibá\~nez; Julián Messina; Juliana Quigua (Inter-American Development Bank (IDB), 2023)
This chapter examines the redistributive preferences of Latin Americans and investigates the factors that shape them. Using a detailed survey in eight Latin American countries, the study sheds new light on redistributive preferences and explores which aspects of redistribution are more popular and among which groups. The roles of selfinterest, perceptions of inequality, values, and the relationship between citizens and the public sphere in shaping attitudes to redistribution are discussed.
Keywords: D3; D63; D73; H71; H72; 330; Personal Income; Redistributive; Latin American countries; Perceptions ofinequality